Hubungan Konsep Dukungan Keluarga Dengan Tingkat Kekambuhan Pada Paisen Skizofrenia - Cindy Tiara; Woro Pramesti; Upik Pebriyani; Ringgo Alfarisi (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Schizophrenia is a mental disorder that will cause deep suffering for individuals and a heavy burden on the family. Family support can function for a variety of intelligence, reason to improve health and family adaptation in life. Objective: to find out whether there is a relationship between family support and relapse in schizophrenia patients in Lampung Province Mental Hospital. Method: This research is a quantitative analytic that uses a cross-sectional research design. The sample in this study is all data of patients suffering from Schizophrenia mental disorders who were treated at the Mental Hospital of Lampung Province in January - May 2020. The sampling technique in this study used a total sampling technique. Data analysis uses univariate analysis to determine the frequency distribution and bivaraite analysis uses chi-squar and fisher's test. Results: It is known that the frequency distribution of emotional support in the majority of schizophrenia patients received 52.6% less emotional support, informational support in the majority of schizophrenia patients received good information support as much as 63.2%, real support in the majority of schizophrenia patients received significant good support as much as 68 , 4%, hope support in schizophrenia patients the majority get good hope support as much as 73.7%, there is a relationship of emotional support with recurrence in schizophrenia patients, there is a relationship of informational support with recurrence in schizophrenia patients, there is a relationship of real support with relapse in schizophrenia patients, there is a relationship between expectation support and recurrence in schizophrenic patients (p-value: 0.001; 0.020; 0.000; 0.004). Conclusion: there is a significant relationship between family support as seen from emotional support, information, real and expectations with relapse in patients with schizophrenia.